Manual of intracytoplasmic sperm injection in human assisted reproduction with other advanced micromanipulation techniques to edit the genetic and cytoplasmic content of the oocyte - Palermo, Gianpiero ca. 20./21. Jh; Nagy, Zsolt Peter ca. 20./21. Jh (Cambridge University Press, 2022)
For around half of the couples who have trouble conceiving the cause of infertility is sperm-related. Intracytoplasmic sperm injection (ICSI) is the most common and successful treatment for male infertility. Here, the pioneers for the technique, along with authorities in the field, describe the underlying science of ICSI and other micromanipulation techniques. Practical advice for performing the techniques is covered in depth, including sperm selection, laser-assisted ICSI, and the use of piezo in ICSI. Examining the safety of ICSI in animal models as well as the impact of ICSI on the health and well-being of the children conceived through the procedure is discussed. This manual is an essential resource for clinical embryologists and laboratory personnel wishing to refine or develop techniques and improve outcomes
Keywords: Cytology